Optimizing fruit production and marketing in Jammu for doubling farmers’ income - Bhat, Anil; Sharma, Akash (Indian Horticulture, 2019)
Diversification to horticultural crops has been found to be the best option as they accure more profit, generate additional employment for rural masses and conserve natural resources. Jammu and Kashmir is well known for its horticultural produce both in India and abroad. The state offers good scope for cultivation of horticultural crops, covering a variety of temperate fruits like apple, pear, peach, plum, apricot, almond, cherry and sub tropical fruits like mango, guava, citrus litchi and phalsa. Besides, medicinal and aromatic plants, floriculture, mushroom, plantation crops and vegetables are cultivated in the state. Horticulture is gaining momentum in the state as its contribution to GSDP remains around 7-8% over the past few years. Farmers’ of study area are diversifying from cereal crops to fruit and vegetable crops to increase their income. Climate of the region is also suitable for growing walnut, ber, apricot, plum, apple etc. Cost and return analysis of fruit revealed that gross returns were `90,000, `17,000 and `10,500 for walnut, apple and amlook plants respectively. Net returns were highest (`92,033.84) in amlook plants followed by walnut (`75,454.67) and apple (`9,583.81). Marketing margin of retailer was highest (`9,130/q) in case of walnut. Producer’s share in consumers’ rupee ranges from 25% in apple and amlook to 48% in walnut.